The Perceived Impact of Parental Depression on the Narrative Construction of Personal Identity: Reflections from Emerging Adults - Kaimal, Girija; Beardslee, William R. (Narrative Works, 2015)
This paper presents a narrative analysis of emerging adults’ perceptions of the impact of parental depression on themselves as they reflected back on their lives in their natal home. Archived interview narratives were analyzed from sixteen respondents from a preventive intervention study of depression in families. The perceptions of parental depression and the perceived impact of parental depression were found to fall into five perspectives: resistance (no impact), negativity (being disadvantaged), ambivalent perspectives (disadvantaged but also sensitized), acceptance (reconciling with loss), and, compassion (sensitivity and caregiving). The findings from the narratives indicated that the perceived impacts of parental depression spanned a spectrum of responses, not all of which were negative. Emerging adults with their own history of depression reported a more resistant or negative perceived impact of parental depression, and more boys than girls narrated perceived negative impacts of parental depression on the self. These perspectives on parental depression derived from the narratives offer clinicians and family therapists a means of understanding the impact of depression on emerging adults’ sense of self. Implications of language usage, such as tense and coherence, are also discussed.